Juvenile chronic arthritis and imaging: comparison of different techniques - E. Filippucci; A. Farina; C. Cervini; W. Grassi (PAGEPress Publications, 2001)
Objective: The aim of this study was to compare imaging findings obtained with different techniques in a patient with juvenile chronic arthritis. Methods: The patient was a 12 years-old child with a 7-months history of arthritis of the first metatarsophalangeal joint of the right foot. The involved area was explored with the following imaging techniques: X-ray, technetium bone scintigraphy, magnetic resonance, gray-scale and power-Doppler ultrasonography. Results: No abnormalities were detected with conventional X-ray. Scintigraphy showed an abnormal uptake of the radionuclide in the first metatarsophalangeal joint of the right foot. Magnetic resonance without contrast revealed clearly evident features of an active process of synovitis. Ultrasonography was able to detect the presence of joint effusion, synovial proliferation, bone erosion of the first metatarsal head. Power-Doppler examination revealed evident signs of soft tissue hyperemia. Conclusions: Comparative assessment of different imaging techniques in this patient with recent-onset juvenile chronic arthritis indicates that high resolution ultrasonography provides the most detailed evaluation of the joint involvement with respect to the other imaging techniques.